Qualidade física de ovos armazenados em diferentes condições de embalagens sob temperatura ambiente - Scatolini-Silva, A. M. [UNESP]; Borba, H. [UNESP]; Giampietro-Ganeco, A. [UNESP]; Souza, P. A. [UNESP]; Boiago, M. M.; Mello, J. L. M. [UNESP]; Vaz, A. B. S. [UNESP] (SciELO Espana/Repisalud, 2013)
The objective was to evaluate the internal quality of white-shelled consume eggs, sanitized or not, stored under different packaging conditions at room temperature. It was used 300 eggs, distributed in a completely randomized experimental design in a 3×2×4+1 factorial arrangement, three packaging conditions (PVC film, partial vacuum, partial vacuum with oxygen gas absorber), storage period (7, 14, 21 and 28 days), sanitized or not, and control (fresh eggs), with four repetitions. At the end of each period the analysis were performed. Partial vacuum condition was able to maintained Haugh unit, and promoted the best results for yolk index. The weight maintenance was better when packaged under vacuum, with or without O2 sachets absorbers. Lower values of water activity were obtained in eggs packed in PVC film, and when the sanitation was performed. It can be concluded that the internal egg quality decreases with storage time sharper in the eggs packed in PVC film, because vacuum has preserved some features of them. With sanitation, the storage conditions of eggs in PVC film should be improved because its internal quality decrease was greatest.
Physical qualitative of stored eggs in different packing condition on room temperature
Keywords: Internal quality; Vacuum